2012
DOI: 10.1111/gcb.12034
|View full text |Cite
|
Sign up to set email alerts
|

Methane emissions from rice paddies natural wetlands, lakes in China: synthesis new estimate

Abstract: Sources of methane (CH 4 ) become highly variable for countries undergoing a heightened period of development due to both human activity and climate change. An urgent need therefore exists to budget key sources of CH 4 , such as wetlands (rice paddies and natural wetlands) and lakes (including reservoirs and ponds), which are sensitive to these changes. For this study, references in relation to CH 4 emissions from rice paddies, natural wetlands, and lakes in China were first reviewed and then reestimated based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
153
5

Year Published

2015
2015
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 200 publications
(168 citation statements)
references
References 131 publications
(247 reference statements)
10
153
5
Order By: Relevance
“…The decrease of CH 4 emissions from rice cultivation over the past decades is confirmed in most inventories, because of the decrease in rice cultivation area, the change in agricultural practices, and a northward shift of rice cultivation since 1970s (e.g. Chen et al, 2013). Furthermore, recent studies revealed that, together, high carbon dioxide concentrations and warmer temperatures predicted for the end of the twenty-first century will about double the amount of methane emitted per kilogramme of rice produced (van Groenigen et al, 2013).…”
Section: Rice Cultivationmentioning
confidence: 96%
See 2 more Smart Citations
“…The decrease of CH 4 emissions from rice cultivation over the past decades is confirmed in most inventories, because of the decrease in rice cultivation area, the change in agricultural practices, and a northward shift of rice cultivation since 1970s (e.g. Chen et al, 2013). Furthermore, recent studies revealed that, together, high carbon dioxide concentrations and warmer temperatures predicted for the end of the twenty-first century will about double the amount of methane emitted per kilogramme of rice produced (van Groenigen et al, 2013).…”
Section: Rice Cultivationmentioning
confidence: 96%
“…The geographical distribution of the emissions is assessed by global (USEPA, 2006(USEPA, , 2012EDGARv4.2FT2010, 2013 and regional Chen et al, 2013;Chen and Prinn, 2006;Yan et al, 2009;Castelán-Ortega et al, 2014; inventories or by land surface models (Spahni et al, 2011;Zhang and Chen, 2014;Ren et al, 2011;Tian et al, 2010Tian et al, , 2011Li et al, 2005;Pathak et al, 2005). The emissions show a seasonal cycle, peaking in the summer months in the extratropics associated with the monsoon and land management.…”
Section: Rice Cultivationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review of the CH 4 flux measurements from different types of natural wetlands and lakes in different regions of China determined by static chamber method, Chen et al [61] estimated that the total CH 4 emissions from natural wetlands and lakes (including reservoirs and ponds) in China were 2.02 TgC a -1 (ranging from 1.85 to 2.40 TgC a -1 ) and 0.35 TgC a -1 (ranging from 0.25 to 0.44 TgC a -1 ), respectively.…”
Section: Fluxes Of Emissions From Reactive Carbon and Creature Ingestmentioning
confidence: 99%
“…, and from 0.012 to 0.21 nmol m ¡2 s ¡1 for CO 2 , CH 4 , and N 2 O, respectively (Wan et al 2010;Chen et al 2013;Liu et al 2013). In recent years, Poyang Lake has suffered severely from water pollution, lake dredging, and water level fluctuations due to human activities and climate change (Lake et al 2000;Fang et al 2006).…”
Section: ¡1mentioning
confidence: 99%